A Connected Generation? Digital Inequalities in Elementary and High School Students According to Age and Socioeconomic Level | Une génération connectée? Inégalités numériques chez les élèves du primaire et du secondaire selon l’âge et le milieu socioéconomique - Collin, Simon; Karsenti, Thierry; Ndimubandi, Alexis; Saffari, Hamid (Canadian Journal of Learning and Technology, 2017)
The objective of this article was to better understand the relationship between students’ age and socioeconomic level, and its influence on students’ digital uses. We conducted a quantitative study of 401 elementary and high school students in Quebec. Four independent variables were initially selected: two related to age (actual age and education level) and two others related to the socioeconomic environment (school poverty index and parents’ employment status). The dependent variable that represented students’ digital uses was the number of different technologies they used weekly. We conducted correlation tests followed by a linear regression analysis. Socioeconomic level appears to have a stronger influence on students’ digital uses compared to age, and explanations for this are proposed. L'objectif de cet article est de mieux comprendre la relation entre l’âge et le milieu socioéconomique des élèves dans leurs usages numériques. Nous avons mené une étude quantitative auprès de 401 élèves du primaire et du secondaire dans la région de Montréal. Quatre variables indépendantes ont été sélectionnées initialement, dont les deux premières renvoient à l'âge (l'âge et l'ordre d'enseignement) alors que les deux dernières renseignent sur le milieu socioéconomique (l'indice de défavorisation des écoles et la situation d'emploi des parents d'élèves). La variable dépendante permettant de rendre compte des usages numériques des élèves était le nombre de technologies qu'ils utilisent sur une base hebdomadaire. Nous avons procédé à une régression linéaire précédée de tests de corrélation. Il en ressort que le niveau socioéconomique semble influencer davantage les usages numériques des élèves que l'âge pour plusieurs raisons explorées dans cette recherche.